2008
DOI: 10.1634/stemcells.2007-0576
|View full text |Cite
|
Sign up to set email alerts
|

Selection Against Undifferentiated Human Embryonic Stem Cells by a Cytotoxic Antibody Recognizing Podocalyxin-Like Protein-1

Abstract: Future therapeutic applications of differentiated human embryonic stem cells (hESC) carry a risk of teratoma formation by contaminating undifferentiated hESC. We generated 10 monoclonal antibodies (mAbs) against surface antigens of undifferentiated hESC, showing strong reactivity against undifferentiated, but not differentiated hESC. The mAbs did not cross react with mouse fibroblasts and showed weak to no reactivity against human embryonal carcinoma cells. Notably, one antibody (mAb 84) is cytotoxic to undiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
196
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(198 citation statements)
references
References 47 publications
1
196
0
1
Order By: Relevance
“…84 mAb was also cytotoxic at 4°C. 51 Interestingly, in the case of 216 mAb cytotoxicity levels increased at this temperature when compared with incubation at 37°C. 44 Additionally, neither the presence of sodium azide nor of EDTA dampened the killing activity of RE2, 70 216 44 and 14F7 66 mAbs, which indicates independence from metabolic energy and calcium influx, respectively.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 87%
See 3 more Smart Citations
“…84 mAb was also cytotoxic at 4°C. 51 Interestingly, in the case of 216 mAb cytotoxicity levels increased at this temperature when compared with incubation at 37°C. 44 Additionally, neither the presence of sodium azide nor of EDTA dampened the killing activity of RE2, 70 216 44 and 14F7 66 mAbs, which indicates independence from metabolic energy and calcium influx, respectively.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 87%
“…Notably, podocalyxin binds to actin through ezrin, 72 and the antigen recognized by 84 mAb is a podocalyxin-like protein. 51 In the case of cells treated with 84 mAb 52 and KID3/RAV12, 48 a disruption of the actin cytoskeleton was observed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, in epithelial cell types that lack EpCAM in adults, upregulation of EpCAM coincides with the early stages of neoplastic change [75]. EpCAM was identified in 2008 as a marker for human embryonic stem cells in an antibody-based screening assay [76]. In 2010, Terris et al [75] revealed that the EpCAM (+) AFP (+) HCC subtype had features of hepatic stem/progenitor cells with gene expression and pathway analyses.…”
Section: Epcammentioning
confidence: 99%